ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MAHASISWA DALAM MEMILIH PROGRAM STUDI PENDIDIKAN MATEMATIKA FKIP UNIVERSITAS MUSAMUS - Khumaeroh Dwi Nur'aini; Maria F. V. Ruslau (Musamus Journal of Mathematics Education, 2018)
This study aims to apply one of the techniques in multivariate statistics namely Factor Analysis to determine the factors that influence the decision of students to choose Mathematics Education Department, Teaching and Education Faculty, Musamus University. Data was collected by distributing questionnaires to 70 students majoring in mathematics education that consists of force in 2015, 2016 and 2017. To analyze the data used factor analysis method with SPSS 20 and obtained that from 25 variables studied can be reduced to only 7 factor. The factors that are formed are the quality factors of the study program, lecturer professionalism, curriculum relevant to the world of work, advice, costs, personal abilities and prospect factors and job opportunities. Keywords: factor analysis, decision, mathematics education